2019
DOI: 10.3168/jds.2019-16873
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling and insulin response in subcutaneous and retroperitoneal adipose tissue in Holstein cows during the periparturient period

Abstract: Adipose tissue response to endocrine stimuli, such as insulin, is crucial for metabolic adaptation at the onset of lactation in dairy cows. However, the exact molecular mechanisms behind this response are not well understood. Thus, the aim of this study was to determine the dynamics in protein expression and phosphorylation of key components in insulin signaling in subcutaneous (SCAT) and retroperitoneal (RPAT) adipose tissues of Holstein dairy cows. Furthermore, by ex vivo examinations, response to insulin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…At least in nonruminants, insulin signaling controls glucose absorption, lipogenesis, lipolysis, and protein synthesis (Kenéz et al, 2019), all of which play vital roles in adipose tissue metabolism. A transient state of insulin resistance around parturition prevents peripheral tissues from using glucose, to guarantee glucose supply for the mammary gland (Contreras et al,…”
Section: Discussionmentioning
confidence: 99%
“…At least in nonruminants, insulin signaling controls glucose absorption, lipogenesis, lipolysis, and protein synthesis (Kenéz et al, 2019), all of which play vital roles in adipose tissue metabolism. A transient state of insulin resistance around parturition prevents peripheral tissues from using glucose, to guarantee glucose supply for the mammary gland (Contreras et al,…”
Section: Discussionmentioning
confidence: 99%
“…This provides evidence that adipose tissue with more ceramides would more suppress insulin sensitivity and have an enhanced sphingolipid dynamic. In contrast to SCAT, Kenéz et al demonstrated that Akt and HSL phosphorylation were greater in the insulin signaling pathway in dairy cow RPAT during the peripartum period [11]. This indicated that RPAT may be more sensitive and responsive in insulin signaling than SCAT.…”
Section: Insulin Resistance Inflammation and Oxidative Stress In Rpat And Scatmentioning
confidence: 99%
“…Retroperitoneal (RPAT) and subcutaneous adipose tissue (SCAT) in dairy cows are suggested to be different in insulin signaling, proinflammatory signaling, and lipolytic activity [11][12][13]. It was demonstrated that RPAT is more responsive than SCAT regarding the insulin signaling pathway, with greater protein kinase B (Akt) and adenosine monophosphate-activated protein kinase (AMPK) phosphorylation, as well as greater fatty acid synthase (FAS) expression, shown in an ex vivo study [11]. Moreover, RPAT had greater proinflammatory cytokine and chemokine messenger RNA [8], and Maceyka and Spiegel [9].…”
Section: Introductionmentioning
confidence: 99%
“…This provides evidence that adipose tissue with more ceramides would more suppress insulin sensitivity and have an enhanced sphingolipid dynamic. In contrast to SCAT, Kenéz et al demonstrated that Akt and HSL phosphorylation were greater in the insulin signaling pathway in dairy cow RPAT during the peripartum period [9]. This indicated that RPAT may be more sensitive and responsive in insulin signaling than SCAT.…”
Section: Insulin Resistance In Ammation and Oxidative Stress In Rpamentioning
confidence: 99%
“…However, adipose metabolism differs to some extent between adipose depots. Retroperitoneal (RPAT) and subcutaneous adipose tissue (SCAT) in dairy cows are suggested to be different in insulin signaling, proin ammatory signaling, and lipolytic activity [9][10][11]. It was demonstrated that RPAT is more responsive than SCAT regarding the insulin signaling pathway, with greater Akt and AMPK phosphorylation, as well as greater FAS expression, shown by an ex vivo study [9].…”
Section: Introductionmentioning
confidence: 99%